Preservation of Native Aortic Valve Flow and Full Hemodynamic Support with the TORVAD Using a Computational Model of the Cardiovascular System. Issue 3 (May 2015) - Gohean, Jeffrey R.; George, Mitchell J.; Chang, Kay-Won; Larson, Erik R.; Pate, Thomas D.; Kurusz, Mark; Longoria, Raul G.; Smalling, Richard W.
<x xml:space="preserve">Abstract</x> This article describes the stroke volume selection and operational design for the toroidal ventricular assist device (TORVAD), a synchronous, positive-displacement ventricular assist device (VAD). A lumped parameter model was used to simulate hemodynamics with the TORVAD compared with those under continuous-flow VAD support. Results from the simulation demonstrated that a TORVAD with a 30 ml stroke volume ejecting with an early diastolic counterpulse provides comparable systemic support to the HeartMate II (HMII) (cardiac output 5.7 L/min up from 3.1 L/min in simulated heart failure). By taking the advantage of synchronous pulsatility, the TORVAD delivers full hemodynamic support with nearly half the VAD flow rate (2.7 L/min compared with 5.3 L/min for the HMII) by allowing the left ventricle to eject during systole and thus preserving native aortic valve flow (3.0 L/min compared with 0.4 L/min for the HMII, down from 3.1 L/min at baseline). The TORVAD also preserves pulse pressure (26.7 mm Hg compared with 12.8 mm Hg for the HMII, down from 29.1 mm Hg at baseline). Preservation of aortic valve flow with synchronous pulsatile support could reduce the high incidence of aortic insufficiency and valve cusp fusion reported in patients supported with continuous-flow VADs.